Efficient Secretory Expression of Leghemoglobin in Saccharomyces cerevisiae - Yiyun Huang; Jingwen Zhou; Jianghua Li; Guocheng Du; Jian Chen; Xinrui Zhao (Fermentation, 2024)
Leghemoglobin (LegH) is a plant-derived hemoglobin that can be used as a food additive to confer red color and meat flavor to plant-based meat products. Although LegH has been expressed in Saccharomyces cerevisiae, the productivity is low at the shaking-flask level, and the downstream process of purification is complicated. Herein, the intracellular expression of LegH reached 151.2 mg/L through initial promoter modification. Then, the fermentation strategy was optimized, and the titer of LegH reached 544.8 mg/L (5.2 mg/L/OD600 per unit yield) in the two-stage fed-batch fermentation in a 5-L fermenter. After the modification of signal peptide and knockout of proteases, the secretory expression of LegH was achieved in recombinant S. cerevisiae, and the final secretory titer of LegH reached 88.5 mg/L at the 5-L fermenter level. Based on the results of this study, the secreted LegH can be widely applied in the fields of food processing and biocatalysis in the future.